2012
DOI: 10.1159/000329553
|View full text |Cite
|
Sign up to set email alerts
|

Failure to Replicate Influence of GRIK4 and GNB3 Polymorphisms on Treatment Outcome in Major Depression

Abstract: In the present study, we aimed to confirm the previous finding of an association between GRIK4 and GNB3 variants (rs195478 and rs5443) and remission and treatment resistance in major depression, using a multicenter sample of 223 patients. We did not find any supporting evidence for such associations. These conflicting data may result from difficulties in the replication of candidate gene association studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 43 publications
2
9
0
Order By: Relevance
“…Furthermore, some studies allowed concomitant drug treatment, such as anxiolytics, mood stabilizers and (in one study) antipsychotics [12]. Finally, one study [11] defined treatment response in a different manner from the remaining four studies. Our ability to detect consistent and significant associations of treatment response with the C allele and CC homozygosity by meta-analysis is perhaps more impressive in light of these differences, which may also indicate the robustness of these effects.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, some studies allowed concomitant drug treatment, such as anxiolytics, mood stabilizers and (in one study) antipsychotics [12]. Finally, one study [11] defined treatment response in a different manner from the remaining four studies. Our ability to detect consistent and significant associations of treatment response with the C allele and CC homozygosity by meta-analysis is perhaps more impressive in light of these differences, which may also indicate the robustness of these effects.…”
Section: Discussionmentioning
confidence: 99%
“…A subsequent study of 82 GRIK4 SNPs in another sample identified a polymorphism with a stronger effect, also enhanced in its effect when combined with HTR2A . While a multicentre study was unable to replicate an effect of this gene on antidepressant response, the Chinese study of Pu et al . also found a significant effect of rs1954787 in GRIK4 on the outcome of antidepressant treatment.…”
Section: Glutamate and Gaba Systemsmentioning
confidence: 97%
“…Pharmacogenetic results are nevertheless inconsistent. Indeed, different SNPs were associated with antidepressant efficacy without any replicated result (rs1954787 [Paddock et al, ], rs12800734 [Horstmann et al, ]), while further studies provided negative findings [Perlis et al, ; Serretti et al, ]. The heterogeneity of treatments may have contributed to the inconsistency among results, since in only one study [Paddock et al, ] citalopram monotherapy was used, while the others allowed mixed regimens, or combinations with mood stabilizers/antipsychotics [Horstmann et al, ].…”
Section: Glutamatergic Systemmentioning
confidence: 99%